SEARCHING FOR SOCIAL JUSTICE - DECENTRALISED GOVERNANCE AND RURAL COMMUNITY SUSTAINABILITY - Costello, Diane; Bishop, Brian (The journal of contemporary issues in business and government, 2008)
Government policies in Australia are heavily directed towards local communities developing their civil society networks to solve complex social, economic and environmental problems. In response, rural communities in Australia have mobilised around principles of sustainability to adapt towards regional self reliance. While decentralised governance is a key mechanism aimed at facilitating local empowerment and community resilience, devolution of responsibility to the local levels also enables governments to distance themselves from decision-making processes that deliver inequitable outcomes. This case study examines the impetus for community engagement and the effectiveness of social mobilisation approaches in delivering socially just outcomes. It is argued that mandatory mechanisms of accountability are vital to ensure that decentralised governance structures are inclusive and facilitate the inter- and intra- generational justice concerns of all community members.